The Importance of Timing, Fundamental Attitudes, and Appropriate Interventions as Key Aspects of Chaplain Suicide Prevention: A European Expert Panel of Mental Health Chaplains - Saliba, Serena Margaret (Journal of pastoral care & counseling, 2023)
An expert panel consisting of six mental health chaplains from several European countries was convened to ascertain the specific contribution of mental health chaplains to suicide prevention, and to generate good practices for suicide prevention. Three themes emerged: (1) the importance of timing; (2) fundamental attitudes of the chaplain towards the patient, and (3) appropriate interventions.